Of Chiefs and Kings: Wendat and British diplomatic traditions, 1838 to 1842 - de Stecher, Annette (Ethnologies, 2015)
“Of Chiefs and Kings” is about the role of Wendat diplomatic traditions, explored through documentary and pictorial evidence and the arts of ceremonial dress. I will describe diplomatic interactions between Wendat and British communities between 1838 and 1842, through which the Wendat affirmed commitments of military and civilian support and asserted a continued Wendat presence in their traditional territories. By their dynamic public representation of Indigenous identity, they denied the romanticized notion of the vanishing race, deeply rooted in the popular imagination. These events marked a particular moment within a Wendat history of diplomatic engagement and intercultural exchange with European leaders, extending back to the early seventeenth century.Wendat and British first-hand accounts furnish perspectives of individual members of each community, while Wendat elders’ recollections of ceremonial traditions give important community knowledge of the significance of these events to the Wendat, at an important time in the history of Wendake and Lower Canada.